Evaluation of gypsum based material as coating agent to improve the efficiency of granular urea fertiliser - Mohd Ibrahim, Khairul Ridzwan (2015)
This study was motivated by the fact that even though urea is the most efficient nitrogen carrier in solid form, it is not efficient in delivering the nutrient to the plant. Approximately 70% of the applied urea fertiliser may be lost to the environment. These losses are due to leaching, decomposition and ammonium volatilization in soil, water and air. The common solutions that are available now which is by coating the urea with polymer or sulphur is not being used by farmers in Malaysia primarily due to the high cost. The effect of these coating materials to the environment after prolonged usage is also now being questioned. The study seeks to explore common readily available materials as an alternative coating material. These materials were Portland cement, gypsum plaster, sulphur and zeolite. The materials were also selected based on their availability, processability and price. All these materials also doubles as either nutrients or conditioner to plant and soil. The materials were varied and blended to produce several coating formulations. A coating drum was used to coat the urea with the formulated materials in a dry blend process. The coated urea samples produced were tested for its particles size distribution, crushing strength and dissolution properties. Its dissolution properties were used to benchmark the effectiveness of the coating. Scanning electron microscope was used to further investigate at a microscopic level the coating thickness and the surface morphology of the samples. Cavities were identified in the coating layer of samples and not seen on SCU which may be the cause for a faster diffusion of the samples compared to SCU. Gypsum plaster and sulphur based coating material were found to have performed better than the other formulations which was 13.8% higher than uncoated urea based on the dissolution analysis performed. This formula was further improved where paraffin wax was experimented as a sealant and showed an improvement in dissolution concentration at 24.2% improved efficiency compared to uncoated urea. The final product achieved the highest efficiency at 26%, a marked improvement in dissolution properties than an uncoated urea. This was produced by pretreating (sieving) the base materials (gypsum plaster and sulphur). It is hope that this product will be commercialized and made available to the farmers as an affordable alternative and solution in the near future. The environment will also be benefitting from a more efficient use of nitrogen fertiliser.